COURT DECISIONS CONCERNING GOODWILL. - Simon, Sidney I. (The Accounting Review, 1956)
Abstract The article discusses the goodwill aspect of valuation of items appearing on the financial statements of a business concern. The definition of goodwill as presented by accountants and the courts have been given consideration. Among them is the definition given by T.H. Sanders, H.R. Hatfield and U. Moore in "A Statement of Accounting Principles," as the excess of the total value of the assets of a going concern over that part of the value which can be allocated to specific assets. All legal cases on the subject agree that the goodwill of a business, though intangible, is property which may be sold as a legitimate asset if it is substantial and may be paid for in capital stock. A cardinal principle in the accounting for goodwill is that it should be shown on the books only when purchased, and then at no more than such purchase price. The article discusses the question whether the cost of extensive advertising, expected to yield benefits for a long period may be capitalized as an asset. It discusses the accounting principle that in transactions the value of goodwill is based on an accurate estimate of prospective net earnings and the amortization of goodwill after its acquisition.